O palacete e a vila Operária: arquitetura residencial do bairro Jacarecanga em Fortaleza-CE de 1910 a 1940 - Melo, Juan Nadson Marques (2021)
The propositions of this work start from the interest in qualitatively analyzing urban residential architectural typologies of the 20th century (1910 - 1940) in the Jacarecanga neighborhood, in Fortaleza-CE, taking as objects of investigation, in this case study, Casa Thomaz Pompeu Sobrinho e Vila São José - the palace and the workers' village, respectively. Such buildings have in common the testimony of a relevant historical context in the formation and characterization of the Jacarecanga neighborhood; however, they differ in composition, morphology, social status of their first residents, etc. Considering that houses are artifacts, and that artifacts are legitimate objects for the study of the populations that created them, the choice of the theme of this work is justified by the relevance that housing plays in daily life, in the formation of space, society and of culture. It is intended to approach these architectural examples not in a merely comparative way, but seeking to understand their spatial specificities in the historical, social and urban context that they share